An electrophysiological assessment of subclinical lead toxicity in children (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: While heavy exposure to inorganic lead is capable of inducing symptomatic neuropathy, subclinical neuropathy due to low level of lead exposure remains to be proved.Objectives: This study was assessed peripheral nerve function in environmental lead exposed primary school children.Methods: Electrophysiological evaluation of peripheral nerve function was done in 17 subclinical lead exposed and 17 non-exposed primary school children in an urban industrial area of Dhaka. Lead exposed children had mean blood lead level (BLL) 20.2 (±5.17) ?gm/ dl. Non-exposed children had BLL 6.2 (±2.82) ?gm/ dl.Results: Electrophysiological evaluation of peripheral nerve function was normal in lead exposed children. Statistical analysis also did not show any significant difference in parameters of nerve function between lead exposed and non-exposed children (p value >0.05).Conclusion: This study did not find any electrophysiological evidence of peripheral nerve dysfunction in the environmental lead exposed children compared to nonexposed.J Shaheed Suhrawardy Med Coll, June 2014, Vol.6(1); 23-26